Influence of salinity on the diversity and composition of carbohydrate metabolism, nitrogen and sulfur cycling genes in lake surface sediments - Liu, Qing; Yang, Jian; Wang, Beichen; Liu, Wen; Hua, Zhengshuang; Jiang, Hongchen (Frontiers in Microbiology, 2022)
Exploring functional gene composition is essential for understanding the biogeochemical functions of lakes. However, little is known about the diversity and composition of biogeochemical cycling genes and their influencing factors in saline lakes. In this study, metagenomic analysis was employed to characterize the diversity and composition of microbial functions predicted from genes involved in carbohydrate metabolisms, nitrogen, and sulfur cycles in 17 surface sediments of Qinghai-Tibetan lakes with salinity ranging from 0.7 to 31.5 g L-1. The relative abundances of carbohydrate-active enzyme (CAZy), nitrogen, and sulfur cycling genes were 92.7-116.5, 15.1-18.7, 50.8-63.9 per 1000 amino acid coding reads, respectively. The Shannon diversity index of CAZy and sulfur cycling genes decreased with increasing salinity, whereas nitrogen cycling gene diversity showed an opposite trend. Relative abundances of many CAZy (i.e., carbohydrate-binding module and carbohydrate esterase), nitrogen (i.e., anammox and organic degradation and synthesis) and sulfur (i.e., dissimilatory sulfur reduction and oxidation, link between inorganic and organic sulfur transformation, sulfur disproportionation and reduction) cycling gene categories decreased with increasing salinity, whereas some CAZy (i.e., auxiliary activity ), nitrogen (i.e., denitrification) and sulfur (i.e., assimilatory sulfate reduction and sulfur oxidation) gene categories showed an increasing trend. The compositions of CAZy, nitrogen, and sulfur cycling genes in the studied lake sediments were significantly (P < 0.05) affected by environmental factors such as salinity, total organic carbon, total nitrogen, and total phosphorus, with salinity having the greatest influence. Together, our findings provide systematic insights into the impact of salinity on the diversity and composition of microbial functions predicted from genes involved in biogeochemical cycles of carbon, nitrogen, and sulfur in lacustrine ecosystems.